2023
DOI: 10.1089/whr.2022.0088
|View full text |Cite
|
Sign up to set email alerts
|

What Black Mothers with Preterm Infants Want for Their Mental Health Care: A Qualitative Study

Abstract: “I think that some culturally sensitive mental health information could have been provided”: What Black mothers with preterm infants want for their mental health care: A qualitative study Background: In the United States, preterm birth (PTB) rates in Black women are 50% higher than in non-Hispanic White and Hispanic mothers. Existing discriminatory sociohistorical and contemporary health care practices have been linked to the alarmingly higher rates of PTB among Black families. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…However, most parents in this sample were married, had at least some higher education, and were employed. Elsewhere, Black and Hispanic mothers of NICU infants have been reported to experience more hospital and home life stressors 43, 44 . Also of note, recent studies have suggested that mothers who reside in lower-income homes and neighborhoods, respectively, report lower anxiety and postpartum traumatic symptoms 22, 24 .…”
Section: Discussionmentioning
confidence: 99%
“…However, most parents in this sample were married, had at least some higher education, and were employed. Elsewhere, Black and Hispanic mothers of NICU infants have been reported to experience more hospital and home life stressors 43, 44 . Also of note, recent studies have suggested that mothers who reside in lower-income homes and neighborhoods, respectively, report lower anxiety and postpartum traumatic symptoms 22, 24 .…”
Section: Discussionmentioning
confidence: 99%